Einführung in das Kapitalstrukturmanagement - Andreas Böger; Thomas Heidorn; Stephan Rupprecht (Frankfurt School of Finance & Management, 2009)
This paper gives an overview of the capital requirements for banks. Regulatory capital is analyzed, followed by the discussion of economic capital. These ideas are used to explain risk adjusted performance measures.
urn:nbn:de:101:1-2009050599
Keywords: 330; Regulatorisches Kapital; ökonomisches Kapital; RAROC; RORAC